Abundance predominates over niche factors as determinant of the frequency of interactions between frugivorous birds and plants - Pizo, Marco A. [UNESP]; Fontanella, Antonio B. [UNESP]; Carlo, Tomás A.; González-Castro, Aarón (My University, 2022)
Neutral and niche factors influence the structure of frugivory and seed dispersal networks. While the former refers to the abundance of interacting species, niche factors refer to traits that mediate interactions between species (e.g., morphology). The challenge is to unravel in which circumstances one kind of factor predominates over the other, or how much variation is explained by each factor. We investigated the relative contributions of abundance and trait matching (considering fruit's size, pulp mass to seed mass ratio, and lipid content, and bird's degree of frugivory, body mass, and gape width) as drivers of the frequency of interactions between frugivorous birds and fleshy fruits in an area of Cerrado second-growth vegetation in Brazil. We expected that the abundance of species would be the most important factor due to the predominance of common small-bodied generalist bird species and small-seeded fleshy-fruited plants. Species abundance was indeed an important factor explaining interactions, although in limited fashion. This is because niche factors also helped to explain bird–plant interaction frequencies in the community, particularly the mass ratio of fruits and, to a lesser extent, their lipid content through its interaction with abundance and its negative correlation with mass ratio. In addition to the importance of both bird and plant abundances, these results underscore the role played by plant functional traits in maintaining community function and ecosystem services even in habitats dominated by common generalist birds and small-seeded plants. Abstract in Portuguese is available with online material.
Keywords: Brazil; Cerrado; frugivory; fruit nutrients; lipid content; seed dispersal; trait matching